Development of Cucurbitaceae family-based e-module in Kudus Regency for learning Spermatophyta - Mohamad Aqib Maulana Wahid; Muhamad Jalil (Scientiae Educatia: Jurnal Pendidikan Sains)
This study aims to 1) determine the validity of the e-module based on the Cucurbitaceae family in the Spermatophyta Class X IPA sub-material. 2) Knowing students' responses as a result of the practicality test on the Cucurbitaceae Family-Based e-module on the Spermatophyta Class X IPA sub-material. This research and development uses a model adopted from the Branch, namely ADDIE, which consists of the Analyze, Design, Development, Implementation, and Evaluation stages. This research was conducted at MA NU Raudlatus Shibyan Peganjaran Bae Kudus. This study used three material expert validators, three media expert validators, and one Biology educator. A limited-scale trial was carried out on all members of class X, totaling 28 people. The results showed that for the validation test by material experts, a score percentage of 91.85% was included in the very valid category, media experts 94.42% were in the very valid category, and Biology educators 78.7% were included in the valid category. The results of the e-module trial for students obtained a score with an average percentage of 78.5%, which was in the feasible category. The local potential-based e-module can be used in the learning process.